The Problems and Demands of Children in Indonesia for the Next Twenty Years - I.G.N. Gde Ranuh (Paediatrica Indonesiana, 1983)
Indonesia as is the case with other developing countries has a "young" population of which 43% conists of a populatdon of underfifteen. Since we know that these children will be the back bone of our nation in the future, efforts to support the endeavour to promote child health will be very beneficial for a long term program. We ought to be happy that the long term health program in Indonesia is directed to the young and productive section of the community and attention is especially given to the low income section or to those in the rural areas.